The promotion effect of biochar on electrochemical degradation of nitrobenzene. (20th January 2020) - Liu, Qiang; Bai, Xiaoqing; Su, Xintong; Huang, Biao; Wang, Bingjia; Zhang, Xiaolei; Ruan, Xiuxiu; Cao, Weimin; Xu, Yunfeng; Qian, Guangren
Abstract: In this study, biochar from the thermal pyrolysis of biomass was introduced into electrolysis to enhance the electrochemical degradation of nitrobenzene (NB). The biochar assisted electrolysis showed significantly enhanced NB removal in addition to the adsorption, where the TOC removal reached over 85%. The reaction rate for the electrolysis with 1 g l −1 of biochar (1.81 × 10 −3 g mg −1 ·min −1 ) was much higher than the test without biochar (0.93 × 10 −3 g mg −1 ·min −1 ). The four level L16 (4 4 ) orthogonal array test confirmed that the biochar played significant roles in NB degradation. Three cycles of adsorption-electrolysis test demonstrated the biochar undergone electroylsis for removing NB could be recycled. The cyclic voltammetry analysis, ·OH free radical scavenging test and NB degradation product analysis suggested that NB on the biochar surface was likely reduced to aniline and the aniline was subsequently mineralized by the hydroxyl radicals which were generated by the electrode. The results of this study highlight the potential of using biochar to assist the electrochemical degradation of organic contaminants in water. Graphical abstract: Image 1 Highlights: Biochar enhanced NB removal during electrolysis. Over 85% of TOC were removed with the aid of biochar. Biochar undergone electrolysis could be recycled. Biochar promoted NB reduction and subsequent mineralization.